Cardiac tumours: non-invasive detection and assessment by gated cardiac blood pool radionuclide imaging. Issue 2 (August 1980) - Pitcher, D; Wainwright, R; Brennand-Roper, D; Deverall, P; Sowton, E; Maisey, M
Abstract : Four patients with cardiac tumours were investigated by gated cardiac blood pool radionuclide imaging and echocardiography. Contrast angiocardiography was performed in three of the cases. Two left atrial tumours were detected by all three techniques. In one of these cases echocardiography alone showed additional mitral valve stenosis, but isotope imaging indicated tumour size more accurately. A large septal mass was detected by all three methods. In this patient echocardiography showed evidence of left ventricular outflow obstruction, confirmed at cardiac catheterisation, but gated isotope imaging provided a more detailed assessment of the abnormal cardiac anatomy. In the fourth case gated isotope imaging detected a large right ventricular tumour which had not been identified by echocardiography. Gated cardiac blood pool isotope imaging is a complementary technique to echocardiography for the non-invasive detection and assessment of cardiac tumours.